2022
DOI: 10.3390/cancers14235779
|View full text |Cite
|
Sign up to set email alerts
|

Wild-Type Isocitrate Dehydrogenase-Dependent Oxidative Decarboxylation and Reductive Carboxylation in Cancer and Their Clinical Significance

Abstract: The human isocitrate dehydrogenase (IDH) gene encodes for the isoenzymes IDH1, 2, and 3, which catalyze the conversion of isocitrate and α-ketoglutarate (α-KG) and are required for normal mammalian metabolism. Isocitrate dehydrogenase 1 and 2 catalyze the reversible conversion of isocitrate to α-KG. Isocitrate dehydrogenase 3 is the key enzyme that mediates the production of α-KG from isocitrate in the tricarboxylic acid (TCA) cycle. In the TCA cycle, the decarboxylation reaction catalyzed by isocitrate dehydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 91 publications
0
8
0
1
Order By: Relevance
“…IDH1 isoform is located in the cytoplasm whereas IDH2 and IDH3 isoforms are placed in mitochondria. IDH1 and 2 catalyze the decarboxylation of isocitrate into AKG rendering NADPH, whilst IDH3 forms AKG, NADH and CO2 from isocitrate [73]. The non-canonical process of formation of isocitrate from AKG and CO2 is named reductive carboxylation, and it is fundamental in hypoxia conditions or when high synthesis of lipids is required [74].…”
Section: Glutaminase Can Trigger Reductive Carboxylation In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…IDH1 isoform is located in the cytoplasm whereas IDH2 and IDH3 isoforms are placed in mitochondria. IDH1 and 2 catalyze the decarboxylation of isocitrate into AKG rendering NADPH, whilst IDH3 forms AKG, NADH and CO2 from isocitrate [73]. The non-canonical process of formation of isocitrate from AKG and CO2 is named reductive carboxylation, and it is fundamental in hypoxia conditions or when high synthesis of lipids is required [74].…”
Section: Glutaminase Can Trigger Reductive Carboxylation In Cancermentioning
confidence: 99%
“…Reductive carboxylation is catalyzed by IDH1/2 through the consumption of NADPH. Of note, NADPH and NADP + cannot cross the mitochondrial membrane, a fact that gives rise to the implication of IDH1/2 in balancing oxidative status in the cytosol and the mitochondria [63,73,74,75]. IDH1 has been related to the scavenging of ROS in the cytoplasm by generating NADPH in this cellular compartment [76].…”
Section: Glutaminase Can Trigger Reductive Carboxylation In Cancermentioning
confidence: 99%
“…The IDH1 isoform is located in the cytoplasm, whereas the IDH2 and IDH3 isoforms are found in mitochondria. IDH1 and -2 catalyze the decarboxylation of isocitrate into AKG, rendering NADPH, while IDH3 forms AKG, and NADH and CO 2 form isocitrate [ 73 ]. The noncanonical process of the formation of isocitrate from AKG and CO 2 is named reductive carboxylation, and it is fundamental in hypoxia conditions or when a high level of the synthesis of lipids is required [ 74 ].…”
Section: Mitochondrial Metabolism Of Glutamine In Cancer: Redox Balancementioning
confidence: 99%
“…Reductive carboxylation is catalyzed by IDH1/2 through the consumption of NADPH. Of note, NADPH and NADP + cannot cross the mitochondrial membrane, a fact that implicates IDH1/2 in the balance of the oxidative status in cytosol and mitochondria [ 63 , 73 , 74 , 75 ]. IDH1 is related to the scavenging of ROS in the cytoplasm by the generation of NADPH in this cellular compartment [ 76 ].…”
Section: Mitochondrial Metabolism Of Glutamine In Cancer: Redox Balancementioning
confidence: 99%
“…This acidification is evident in the glioma cells of fast proliferation, which results in the production of significant amounts of metabolic waste products including lactate and carbon dioxide by consuming nutrients and oxygen from the tissues around them (DeBerardinis et al, 2007; Lugano et al, 2020; Tanaka et al, 2021). This acidification has a range of pathophysiological consequences, including disrupting normal cellular metabolism, altering the function of various proteins and enzymes, and promoting the growth and survival of glioma cells (Pienkowski et al, 2021; Alzial et al, 2022; He et al, 2022). Consolidated data from multiple investigations have revealed that tumor masses can have varied pH levels ranging from 7.4-6.2 units and can decrease to 5.5-3.4 units or even below (Webb et al, 2011; Kato et al, 2013; Chen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%